The Influence of Interpersonal Communication Skills, Parenting Styles, AI Integration, and School Environment on Learning Motivation - Hidayat Mukti; Siti Rumenta; Forme Onray Siallagan (Institut Nalanda, 2023)
This study investigates the intricate dynamics among interpersonal communication skills, parenting styles, AI integration, and school environment in influencing learning motivation. The research aims to discern how these factors interplay and impact students' motivation to learn. Employing a phenomenological research model, the study employs purposive sampling to select participants, consisting of students, parents, educators, and AI integration specialists. Data collected through interviews and observations are analyzed using thematic analysis techniques. Preliminary findings reveal multifaceted relationships between these variables, highlighting the significant role of supportive interpersonal communication, authoritative parenting styles, effective AI integration, and conducive school environments in fostering intrinsic motivation among learners. This research contributes to a nuanced understanding of the complex mechanisms underlying learning motivation in contemporary educational settings.